Integrating Citizenship Education In The National Curriculum: Challenges And Opportunities - Aba, Akbar; Ilmiawan, Ilmiawan; Nur, Jumiati (Jurnal Edukasi Terkini, 2024)
Citizenship Education (PKn) plays a vital role in developing citizens who are intelligent, responsible and committed to the values of good citizenship. This article explores the importance of Civics in shaping the character and attitudes of citizens who can contribute positively to society and the country. By analyzing the objectives and curriculum of Civics, this article emphasizes aspects such as developing civic literacy, understanding the rights and obligations of citizens, and instilling Pancasila values as the nation's moral and ideological foundation. This article also highlights the challenges and opportunities in implementing effective Civics learning, including the importance of innovative and contextual teaching methods and the role of teachers as facilitators and role models for students. Thus, this article contributes to the discussion about how Civics can be optimized to form a young generation who is intelligent, responsible and has a strong sense of nationality.